Improving the Definition of the Notion “Goods” for Accounting Purposes of Trade Enterprises - M. V. Olshanska; Yu. Ya. Fal (Naukovij Vìsnik Nacìonalʹnoï Akademìï Statistiki, Oblìku ta Auditu, 2019)
Trade as a type of activity is carried out by the majority of enterprises, both in Ukraine and abroad. Trade in Ukraine was rapidly growing in 2012–2017, with re-orienting to EU markets, which modifies the requirements to goods, approaches to their management and accounting. This raises the importance of theoretical studies associated with interpretation of the notion “goods”. The article aims to propose an optimized definition of “goods” for accounting purposes of trade enterprises by making a review of the existing approaches to this category definition, found in theoretical studies and normative documents.